The future of nuclear power in France: An analysis of the costs of phasing-out - Raimund Malischek; Johannes Trüby (Institute of Energy Economics at the University of Cologne (EWI), 2014)
Nuclear power is an important pillar in electricity generation in France. However, France's nuclear power plant fleet is ageing, and the possibility of reducing its share in power generation or even a complete phaseout has been increasingly discussed. Our research therefore focuses on three questions: First, what are the costs of phasing-out nuclear power in France under different scenarios? Second, who has to bear these costs, i.e., how much of the costs will be passed on to the rest of the European power system? And third, what effect does the uncertainty regarding future nuclear policy in France have on system costs? Applying a stochastic optimization model for the European electricity system, we show that additional system costs in France of a nuclear phase-out amount up to 76 billion Euro 2010. Additional costs are mostly borne by the French power system. Surprisingly, we find that the costs of uncertainty are rather limited. Based on our results, we conclude that a commitment regarding nuclear policy reform is only mildly beneficial in terms of system costs.
Keywords: C61; Q40; Q48; L94; 330; nuclear policy; uncertainty; investment; France; electricity market modeling